The Indian Steps - Shoemaker, Henry W. (Penn State University Press, 2025)
Originally published in 1912 by the Bright Printing Company, The Indian Steps belongs to Henry Shoemaker’s robust corpus of tales and legends based on the folklore of Pennsylvania. This early Shoemaker collection of literary folklore paints a colorful picture of the natural landscape, folklore, and society of Central Pennsylvania, which Henry Shoemaker held dear. Beginning with the notable legend of the Indian Steps near Stone Valley, this volume includes stories about fantastical fairies, mysterious hermits, serendipitous romance, Native American legends, ghosts, and hauntings. The volume places a special focus on familiar locations in Centre County, such as Tussey Mountain, Black Moshannon, and Stone Valley. The text, reproduced in facsimile for the first time since its original printing, includes period photographs by W. T. Clarke.